Assessment of the financial autonomy of rural municipalities - Astrida Miceikienė; Laima Skauronė; Ričardas Krikštolaitis (Economies, 2021)
The present study demonstrates the possibilities for assessment of the financial autonomy of rural municipalities using the TOPSIS method. The study aimed to design and empirically verify the model for assessment of the financial autonomy of rural municipalities. As a result of the empirical study, an integrated system for assessment of the financial autonomy of rural municipalities was designed. The applicability of the TOPSIS method is demonstrated by the assessment of the financial autonomy of rural municipalities performed for two regions of Lithuania in the period 2009-2019. The empirical study showed that medium-low level of financial autonomy was characteristic of all the rural municipalities in the selected regions. On one hand, the findings suggested the presence of 'convenient dependence' of the rural municipalities on the centralised allocation. On the other hand, they signalled the lack of the incentives for the rural municipalities to make use of the capacities and create sustainable, stable economic and social prospects.
Keywords: 330; financial autonomy; TOPSIS method; rural municipalities